Advances in the Photovoltaic Field Through Light Manipulation. - Validzic, Ivana (Cambridge Scholars Publishing, 2022)
Developments in instruments and digitalization have today produced a need for uniformity in science, which has largely eliminated the innovative element of scientific research. The sun's energy can be harnessed for many applications by converting energy from one form to another. The most important of these are generating electricity with photovoltaic cells and heating water. Today, only around 1% of global renewable energy comes from solar technologies. It is hard to believe there is such a powerful source of energy as the sun without us being able to use it more efficiently. This book presents.